Comparative effect of two doses of growth hormone for growth hormone deficiency. The Dutch Growth Hormone Working Group. Issue 1 (July 1994) - De Muinck Keizer-Schrama, S; Rikken, B; Hokken-Koelega, A; Wit, J M; Drop, S
Abstract : The comparative effect and safety of 2 IU compared with 4 IU/m2/day of recombinant human growth hormone (rhGH) was studied in 38 growth hormone deficient children regarding the impact of several factors on short term (one year) and long term (three year) growth response. In 21 newly diagnosed patients, three years of rhGH treatment resulted in a significant increase of height velocity SD score, height SD score, and predicted adult height SD score, irrespective of rhGH dose. In 17 transfer patients (previously treated with 12 IU rhGH/m2/week) 4 IU/m2/day resulted in a significantly higher height velocity SD score and height SD score for chronological age than 2 IU/m2/day, while more of them reached their target range or showed a substantial height SD score increment. Height SD score for bone age and predicted adult height SD score only increased significantly with 4 IU rhGH. After one year of rhGH treatment, new patients showed significant negative correlation between delta height SD score with age and baseline insulin-like growth factor I (IGF-I) SD score, and positive correlation with rhGH dose. After three years of treatment, delta height SD score for chronological age was significantly, negatively correlated with age and baseline 'corrected' height SD score (height SD score for chronological age minus target height SD score). There was no significant correlation with rhGH dose. Prolonged treatment with either dose had no adverse effect on IGF-I concentrations, carbohydrate or lipid metabolism. As early age and divergence between height SD score and target height SD score seem more important for growth response than rhGH dose, it is recommended that treatment starts early with 2 IU rhGH/m(2)/day and the dose is doubled if growth is insufficient after several years of treatment.